Factors That Influence the Consumer Purchase Intention in Social Media Websites - Kian, Tan Pei; Boon, Goh Hong; Lian Fong, Stany Wee; Jian Ai, Yeow (International Journal of Supply Chain Management, 2017)
The market shares of different online social networking websites have grown rapidly in the recent years. The growth of social media and social network not only created a new way for people to communicate and interact with each other regardless of geographical distance, it also created a new style of commerce at the same time, known as social commerce. Social commerce evolved from E-commerce and it exists in a community where consumers can share and refer experiences of electronic transactions with each other before making purchase decision. Hence, the purpose of this study is to examine the factors that influence consumer purchase intention in social media websites. Majority of previous literatures focus more on E-commerce. In order to have a deeper understanding on consumer purchase intention in social media websites, a research model is designed suggest that perceived ease of use, perceived usefulness, social influences, trust and perceived enjoyment may influence consumer purchase intention in social media websites. This model also suggests that there may have differences of consumer purchase intention in social media websites among demographic characteristics. Online questionnaires are conducted during this study. Also, several data analyses such as reliability test, descriptive test, t-test, One-Way ANOVA and Multiple Linear Regression are conducted. The result of this study proved that consumer perceived ease of use, consumer perceived usefulness, social influences, trust and consumer perceived enjoyment have an impact on consumer purchase intention in social media websites. Lastly, there is a difference of consumer purchase intention in social media websites among Malaysian consumer with different demographic characteristics.